Age-related presentation of acute type A aortic dissection. (November 2018) - Malvindi, Pietro Giorgio; Votano, Daniela; Ashoub, Ahmed; Modi, Amit; Miskolczi, Szabolcs; Velissaris, Theodore; Barlow, Clifford; Ohri, Sunil; Tsang, Geoffrey; Livesey, Steven; Göbölös, Laszlo
Background: We evaluated the clinical and anatomic presentations of acute type A aortic dissection according to patient age. Methods: We retrospectively reviewed 235 consecutive patients who underwent acute type A dissection repair between January 2000 and December 2014. The influence of age on anatomical and clinical presentation, surgical management in the entire cohort and also after exclusion of patients with known connective tissue disorders was assessed using logistic regression. Results: Males presented with type A acute aortic dissection at a younger age than females. Acute onset with signs of myocardial ischemia, connective tissue disorders, or bicuspid aortic valve characterized the younger population. Extension to the coronary sinus(es) ( p = 0.0003), descending thoracic aorta ( p = 0.016), and abdominal aorta ( p = 0.029), and an intimal tear at the level of the aortic root ( p = 0.0017) correlated inversely with patient age. Similar findings were obtained after exclusion of patients with connective tissue disorders or a bicuspid aortic valve. Conclusions: More frequent proximal and distal progression of the dissection flap occurs in younger patients with acute type A aortic dissection. Older age is associated with a lower probability of an intimal tear at the level of the sinus of Valsalva. These findings, associated with prognostic implications, account for the choice of more radical proximal procedures for repair of aortic dissection in younger patients.